ALLELOPATHIC EFFECTS OF HUMUS FOREST SOIL OF HIPPOPHAE RHAMNOIDES, CARAGANA KORSHINSKII AND AMORPHA FRUTICOSA ON MEDICINAL PLANTS - Xiao, Liang; Xiaobo, Liu; Xiaoxi, Zhang; Zengwen, Liu; Gaudel, Gokul; Jizhou, Zhang (Emirates Journal of Food and Agriculture, 2017)
Allelopathic effect is an important problem in constructing tree-herb complex system. In order to choose medicinal plants which may be suitable for growth under the forests of the Loess Plateau, humus soil of 3 types of broad-leaved forests was collected as medium to conduct a pot-culture experiment. The allelopathic effects of the forest soil on the growth and physiology of 11 types of medicinal plant were studied. The results showed that Belamcanda chinensis, Arisaema heterophyllum, Saposhnikovia divaricata, Bupleurum chinense and Isatis tinctoria, which were significantly inhibited in humus soil of Hippophae rhamnoides forest should avoid to be planted in this forest; B. Chinense, Glycyrrhiza uralensis, B. Chinensis, Astragalus membranaceus and A. heterophyllu, which were significantly inhibited in the humus soil of Caragana korshinskii should avoid to be planted; in addition, A. heterophyllum, A. membranaceus, I. Tinctoria and B. Chinensis, which were significantly inhibited in the humus soil of Amorpha fruticosa should avoid to be planted.